2009
DOI: 10.1021/jp905889z
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Amyloid-β (1−42) Monomer Absorbed To Model Phospholipid Bilayers: A Molecular Dynamics Study

Abstract: The amyloid-beta (Abeta) peptide, the 39 to 43 amino acid peptide that plays a substantial role in Alzheimer's disease, has been shown to interact strongly with lipids both in vitro and in vivo. Abeta-lipid interactions have been proposed as a considerable factor in accelerating Abeta aggregation through the templating role of membranes in aggregation disorders. Previous work has shown that anionic lipids are able to significantly increase Abeta aggregation rate and induce a structural conversion in Abeta from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 53 publications
10
81
0
Order By: Relevance
“…Simulations addressing inserted Aß as the initial state show a wide range of behavior from anchoring to the extracellular membrane interface, 24,27,28 to ejection from the membrane. 26,31 However, few simulations 26 have addressed Aß interactions with membranes composed of CHOL and unsaturated lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations addressing inserted Aß as the initial state show a wide range of behavior from anchoring to the extracellular membrane interface, 24,27,28 to ejection from the membrane. 26,31 However, few simulations 26 have addressed Aß interactions with membranes composed of CHOL and unsaturated lipids.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29] Simulation of aggregation and release processes 26,30,31 are particularly relevant to the work presented here because they can compete with unfolding, penetration, and binding phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…All previous MD studies of Ab in membranes 17,18,27,36,[39][40][41] have consisted of only a single lipid type or an implicit model representing a membrane. In this work, however, we have explored numerous explicit model membranes, including the most complex lipid environments in which Ab has been simulated to date, rafts that correspond very closely to the lipid matrix that Ab encounters upon its production following c-secretase cleavage of APP.…”
Section: Discussionmentioning
confidence: 99%
“…Davis et al have reported that Aβ 1-42 monomer with initial α-helical or β-hairpin structure unfolds into random coils and turns on the zwitterionic DPPC bilayer while remaining in its initial α-helical or β-hairpin structure on the anionic DOPS bilayer. 39,40 In addition to the study of Aβ bound to the membrane surface, Lemkul et al 41,43 (GROMACS96 with an explicit membrane), Miyashita et al 44 (CHARMM22 with implicit GBSW membrane and replica-exchange MD), and Strodel et al 42 (CHARMM19 with implicit IMM1 membrane and the Basin-hopping method) have used different computational approaches and force fields to study the conformation of Aβ 1-40/42 monomer inserted in the membrane. Lemkul et al found that the N-terminal residues of 1-24/1-28 retain its α-helical conformation within the DPPC bilayer, but the C-terminal residues of 25-42/29-42 adopt a disordered structure on the DPPC surface.…”
Section: Electrostatic Interactions Are Dominant Forces Contributing mentioning
confidence: 99%